Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Cabul Studi Putusan Pengadilan Negeri Sungguminasa No.8/Pid.Sus-Anak/2017/PN.Sgm - Vinamya Audina Marpaung; Madiasa Ablisar; Marlina Marlina; Edi Yunara (USU LAW JOURNAL, 2019)
Abstract. Children are the next generation of generation and successors of existing development struggles. Children are the mandate as well as the gift of God Almighty that we always have to guard because in him the dignity, dignity and rights as human beings must be upheld. Child rights are part of human rights contained in the 1945 Constitution and the United Nations Convention on the Rights of the Child. Criminal acts of sexual abuse committed by children in the Sungguminasa District Court No.8 / Pid.Sus-Anak / 2017 / PN.Sgm. Stating the child above, has been proven legally and convincingly guilty of committing a criminal act "intentionally persuading the child to commit an obscene act" as a single charge of the public prosecutor. Dropping the criminal offense to a child is therefore a prison sentence of 1 (one) year and 8 (eight) months and job training in LPKA (Child Development Special Institution) Class II B in Maros, for 6 (six) months. This research uses normative research method is research that examines the principles or principles of law, legal systematics, the level of vertical and horizontal synchronization, comparison of law, and legal history, positive legal norms, principles, principles, and doctrines -doctrine law. The nature of this research is descriptive and prescription. In addition to describing or describing the subject and the motorcycle taxi as well as an analysis of the problems that have been formulated. Provide legal arguments, then make an assessment (perscription) regarding right or wrong or how it should be according to law against facts or legal events. Legal protection for child offenders starting from the stages of investigation, prosecution, trial and arriving at child care in LPKA must be carried out in accordance with the provisions of the legislation. In the implementation of children's rights as perpetrators of obscene crimes, children have the right to enjoy all their rights in accordance with the provisions contained.   Keywords: child protection, child criminal actor, obscene.